Keabsahan Wali Ijbār dalam Perspektif Fikih Islam (Studi Analisis Pendapat Imam Syafi’i): The Validity of the Guardian of Ijbār in the Perspective of Islamic Jurisprudence (Analytical Study of Imam Shafi'i's Opinions) - Muhammad Istiqamah; Rustam Koly; Muhammad, Muhammad; Muhammad Faris (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This study discusses the validity of the guardian of ijbār in the perspective of Islamic jurisprudence, with a particular focus on the opinion of Imam Shafi'i. A guardian of ijbār is one who has the authority to marry off a woman under his guardianship without her explicit consent, especially if she is a virgin. The objective of this study is to examine the legal foundations and legitimacy of ijbār, as well as the conditions under which it is applicable according to the Shafi'i school of thought. This research is qualitative in nature and employs a library research method, using a normative juridical and philosophical approach. The findings reveal that the concept of ijbār is strongly rooted in the Qur'an and Hadith, and is supported by classical Islamic scholars, particularly Imam Shafi'i through works such as al-Umm. In his view, the right of ijbār is limited only to the father and paternal grandfather, and must meet certain conditions, including the absence of hostility, compatibility of the prospective husband, and a reasonable dowry. This right aims to protect women from poor marriage decisions that may endanger their well-being. However, it must be implemented with consideration of mutual consultation to prevent injustice.